2009
DOI: 10.1039/b909641h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective electrophilic trifluoromethylation of β-keto esters with Umemoto reagents induced by chiral nonracemic guanidines

Abstract: Chiral nonracemic guanidines act as Brønsted bases to generate guanidinium enolates for the enantioselective electrophilic trifluoromethylation of beta-keto esters by means of S-(trifluoromethyl)dibenzothiophenium tetrafluoroborate (Umemoto reagent) with good enantioselectivity of 60-70% range. Despite the fact that the ees are still improvable, the model reported in this work could spark the imagination of chemists to design new chiral bases to improve the stereochemical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 76 publications
0
27
0
3
Order By: Relevance
“…[1][2][3][4][5] Indeed, the appropriate introductiono fafluorine atom or a fluorinated group can drastically affect the biological and physical properties of am olecule andi ts physiological behavior with respect to the modeo fa ction and metabolism. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The introduction of at rifluoromethylg roup in an enantioselective manner is one of the most challengings ynthetic problems. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The introduction of at rifluoromethylg roup in an enantioselective manner is one of the most challengings ynthetic problems.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Indeed, the appropriate introductiono fafluorine atom or a fluorinated group can drastically affect the biological and physical properties of am olecule andi ts physiological behavior with respect to the modeo fa ction and metabolism. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The introduction of at rifluoromethylg roup in an enantioselective manner is one of the most challengings ynthetic problems. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The introduction of at rifluoromethylg roup in an enantioselective manner is one of the most challengings ynthetic problems.…”
mentioning
confidence: 99%
“…[321] Spätere Methoden zur enantioselektiven a-Trifluormethylierung von Carbonylverbindungen nutzen die Bildung chiraler Enamine unter Organokatalyse. [321] Spätere Methoden zur enantioselektiven a-Trifluormethylierung von Carbonylverbindungen nutzen die Bildung chiraler Enamine unter Organokatalyse.…”
Section: Fluorierungenunclassified
“…The best enantiomeric excess was 45% for 20% yield [17]. In 2008–2009, we found that chiral nonracemic cinchona alkaloids and guanidines act as Brønsted bases to generate ammonium or guanidinium enolates for the enantioselective electrophilic trifluoromethylation of β-keto esters with Umemoto reagents with good enantioselectivities in the range 60–71% (Scheme 9) [1819]. …”
Section: Reviewmentioning
confidence: 99%